Contribution to the evaluation of clinical prognostic factors in canine lymphoma - Henriques, Joaquim José Garcia Pereira (2022)
Non-Hodgkin Lymphoma (NHL) is the most common hematopoietic cancer in dogs, from which up to 50% of the cases are diffuse large B-cell lymphomas (DLBCL). The etiology, like in humans, is believed to be multifactorial. To the date, the best response rate and best survival times are offered by a combination therapy including cyclophosphamide, vincristine, doxorubicin and prednisolone, known by the acronym of CHOP. Infectious agents, namely vector-borne agents (VBA), can induce chronic B cell stimulation and immune deregulation permitting lymphomagenesis. Also, there are several reports in literature associating NHL with VBA, namely from the genus Borrelia and Leishmania mimicking or co-existing with hematopoietic malignancies either in humans or dogs. Vector-borne agents can induce haematological and clinical changes in hosts that, when existing in cancer patients, can either mislead the interpretation of clinical signs or interfere with recognized prognostic markers, namely blood cell populations. Prognosis, after quality of life, is determinant in veterinary oncology to further proceed with a treatment. Short survival times and therapy response rates determine the option for a non standard-of-care treatment or, lately, animal euthanasia without treatment. Consequently, easy to perform, “bench-to-bedside” widely available and cost-effective prognostic markers are fundamental to obtain client financial compliance and support treatment planning and disease outcome. Obtaining serological results on vector-borne agents or haematological information trough a total blood cell count and biochemical parameters are widely available and cost effective either by an “in-house” laboratory or trough commercial laboratories. Having in mind the existing published literature on human medicine regarding haematological parameters as prognostic indicators in lymphoma and the scarse information on the veterinary field, we aimed to: 1) investigate the prevalence of infection by four vector-borne agents (Leishmania infantum, Ehrlichia canis, Anaplasma phagocytophilum and Bartonella henselae), its potential role in lymphomagenesis and its possible association with the tumour subtype and with the haematological alterations present in dogs with lymphoma and, 2) determine the prognostic value of dogs’ sex, neutered status, clinical stage, presence of anaemia, presence of neutrophilia, presence of thrombocytopenia and the ratios lymphocyte-to-monocyte (LMR), neutrophil-tolymphocyte (NLR), platelet-to-lymphocyte (PLR) and platelet-to-neutrophil (PNR) in canine DLBCL that were naïve for treatment, fully staged and received chemotherapy with a 19 week-CHOP protocol. All dogs tested negative for B. henselae, A. phagocytophilum and E. canis by both serology and molecular detection. Regarding L. infantum, 8,2% of the dogs had a positive serologic result. Leishmania infantum DNA was detected in two samples of diffuse large B-cell lymphoma (DLBCL). These results show an increased, but not significant, seropositivity (8,2%, p=0,201) and molecular detection (3,3%, p=0,166), for L. infantum in dogs with lymphoma, when compared to matched historic controls in the same geographical area. In the second study, PNR showed to be an independent prognostic marker (p≤0,001) for TTPR at 180 and 365 days. Dogs with a PNR above 0,032 were more likely to progress before 180 days (sensitivity 46,5%, specificity 87,5%, p=0,004). On univariate analysis, NLR showed a prognostic significance for LSSR at 180 (p=0,006) and 365 days (p=0,009). A baseline NLR value below 7,45 was positively associated with survival at 180 days (sensitivity of 52%, specificity of 85.3%, p=0.025). The presence of substage b, was associated with early lymphoma progression and decreased survival at 180 days (p =0.031). Anaemia significantly reduced LSSR at 365 days (p=0,028). Although it was not possible to identify, in the first study, any significant association between canine lymphoma and the studied VBA, it was of extreme importance for the discussion of the second study on the possible effects on peripheral blood cell dynamics caused by the CBVD studied. Further studies, following dogs trough their CVBD disease evolution, are worthwhile and may help clarify a possible role of these agents in lymphomagenesis. This is the first study evaluating PLR and PNR in canine DLBCL and demonstrates that PNR could be a predictor of early lymphoma progression. Since peripheral blood cell composition can be affected by several non-oncological causes, the development of larger multicenter studies with homogeneous inclusion criteria could help to better determine the true predictive values of blood cell ratios in dogs suffering from DLBCL treated with CHOP chemotherapy.